Norman Barrett (1903–1979): Unorthodox pioneer of thoracic and oesophageal surgery. (May 2016) - Edison, E; Agha, R; Camm, C
It is an interesting quirk of medical history that the legacy of Norman Barrett most ostensibly lies in the name of a disease the he was quite emphatically wrong about, at least when he first described it. Indeed, there are those who argue to remove the eponym in favour of the title 'Columnar Lined Epithelium', in part because of what little Barrett actually had to do with the correct initial characterisation of this disease. Yet the sum of Norman Barrett's contributions to modern medicine is much more than a mistaken characterisation of a pathological process. Barrett was truly a pioneer of chest surgery in the UK – a speciality in its embryonic stages when he first qualified. He was also renowned as a teacher and academic of the highest calibre. In tracing the story of his life we can see how his natural attributes, life experiences and keen appreciation of the arts (especially history) facilitated personal success and such sharp insight into the vagaries of modern academic medicine.